An appetite for wonder [compact disc, unabridged] : the making of a scientist, a memoir - Dawkins, Richard, 1941- (Harper Audio, 2013)
From his idyllic childhood in colonial Kenya to the raucous debates at Berkeley and Oxford, Dawkins shares here, for the first time, the details of his intellectual awakening and the thrilling path to the creation of The Selfish Gene.